Soluble transferrin receptor as an indicator of iron deficiency and febrile seizures - Salma Salma; Rita Arifin; Erial Bahar; Rini Purnamasari (Indonesian Pediatric Society Publishing House, 2015)
Background Iron deficiency (ID) has a high incidence in Indonesia, and is a risk factor for febrile seizures. The most suitable assay to detect iron deficiency in the presence of inflammation has not yet been defined. An indicator of ID unaffected by inflammation is needed, soluble transferrin receptor (sTfR) may be such an indicator. Objective To evaluate ID as a risk factor for febrile seizures in children with inflammation by sTfR measurements. Method We conducted an age-matched, case-control study, focused on children experiencing on acute illnesses at the time. Subjects were 80 children matched by age (40 in the case group with febrile seizures, and 40 in the control group who were febrile without seizures) aged 3 months to 5 years in Mohammad Hoesin Hospital, Palembang from February to August 2013. Subjects' clinical data and sTfR levels were recorded. Risk factors were analyzed with odd ratios and 95% confident intervals. The sTfR level cut-off point as a predictor of febrile seizures was also defined. Other risk factors were analyzed with multivariate logistic regression test. Results Mean sTfR levels were 41.36 (SD 2.04) nmol/L in the case group and 33.09 (SD 1.02) nmol/L in the control group. Multivariate analysis revealed ID and iron deficient anemia (IDA), as measured by sTfR levels, to be risk factors for febrile seizures (adjusted OR=3.9; 95%CI 1.41 to 10.8; P=0.007 and OR 3.27; 95%CI 1.21 to 8.84; P=0.017, respectively). The sTfR level cut-off point that could be used as a predictor of febrile seizures was 37nmol/L. Conclusion Iron deficiency as measured by increased sTfR is a risk factor for febrile seizures in children.